EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH TERHADAP KEAKTIFAN SISWA DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP - Puspitasari, Elisabeth Ungaria Ega; Ariyanti, Gregoria (Educatio Vitae, 2015)
This research aims to determine (1) whether or not there is some difference of the students’ activation between groups of students who are taught by the conventional learning and the students’ activation of groups of students who are taught by the problem based learning, (2) whether or not there is some difference of the students’ mathematics studying achievement between groups of students who are taught by the conventional learning and the students’ mathematics studying achievement of groups of students who are taught by the problem based learning. This research is a quantitative Pre-Experimental Designs. It was implemented to the second semester students of the academic year 2014/2015 of Junior High School 4 Madiun with the class VII as population. While, the sample of this research was the students of the class VII J as control class using conventional learning, then class VII H as an experimental class using problem based learning The techniques of data collection used were test and non test (observation). The instrument used in the test was studying achievement test and observation sheet of students’ activation. Test instrument was validated and tested to determine the reliability. Based on the hypothesis’ test obtained: (1) there is no difference of the students’ activation between groups of students who are taught by the conventional learning and groups of students who are taught by the problem based learning. (2) there is some difference of the students’ mathematics studying achievement between groups of students who are taught by the conventional learning and groups of students who are taught by the problem based learning. Keywords: Problem Based Learning, Students’ Activation, Students’ Mathematics Studying Achievement.